Asbestos Exposures, Mesothelioma Incidence and Mortality, and Awareness by General Practitioners in the Molise Region, Central Italy. Issue 2 (February 2018) - Ripabelli, Giancarlo; Tamburro, Manuela; Di Tella, Domiziana; Carrozza, Francesco; Sammarco, Michela Lucia
Abstract : Objective: The aim of this study was to evaluate environmental asbestos sources, mesothelioma incidence and mortality, and awareness on asbestos-related diseases (ARDs) by general practitioners (GPs) in Molise Region. Methods: The contaminated sites in three towns were identified by census; mesothelioma incidence (2000 to 2012) and mortality (2003 to 2013) was achieved from local registries; GPs were interviewed on practiced population's exposures and ARDs diagnosis. Results: About 54.3% of visited sites were contaminated (71.2% by friable asbestos) and 38.8% was extremely damaged. Over above time-periods, 32 mesothelioma cases (62.5% males, 25% in people aged 70 to 75 years) and 27 deaths (90% males, 69 ± 10 years, 70.4% pleural mesothelioma) have been reported. A total of 122 GPs were interviewed who had diagnosed 40 mesothelioma and 28 asbestosis cases. Conclusion: There is the need of remediation/removal interventions for contaminated sites and of strategies to increase GPs awareness on asbestos risks for better patients' management.